Anion selectivity in ion exchange reactions with surface functionalized ionosilicas. Issue 15 (21st April 2015) - Petrova, Maria; Guigue, Mireille; Venault, Laurent; Moisy, Philippe; Hesemann, Peter
<x xml:space="preserve">Abstract</x> Mesoporous imidazolium functionalized ionosilicas have been investigated as anion exchange materials for the adsorption of oxo-anions in aqueous media. Pertechnetate exchange in the presence of competing anionic species revealed Hofmeister selectivity.